Challenges Faced by Small, Medium, and Micro Enterprises in Implementing Entrepreneurial Leadership Styles - Muenda, Mutshidza Kingsley; Nkondo, Livhuwani Gladys (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: Entrepreneurial leadership is important in fostering innovation and long-term success. This study explores the challenges South African Small, Medium, and Micro Enterprises (SMME) face in adopting entrepreneurial leadership styles; these challenges are particularly pronounced in the South African context due to economic volatility, limited access to capital, and a lack of formal business education among entrepreneurs. Design/methodology/approach: This study employed a rigorous qualitative research design, conducting semi-structured interviews with 16 SMME leaders from diverse industries in the Vhembe District. Findings: The data were meticulously analysed using thematic analysis, revealing the critical leadership challenges and potential solutions. Research limitations/implications: The study has unearthed significant barriers to adopting entrepreneurial leadership styles, including internal resistance, external regulatory and economic pressures, resource limitations, and a lack of leadership awareness. These factors hinder innovation and long-term growth among SMMEs and provide crucial insights for understanding leadership dynamics in resource-constrained environments. Practical implications: The study's findings offer actionable recommendations for overcoming these barriers. It underscores the importance of cultivating an entrepreneurial mindset within SMMEs. These strategies can enable more effective leadership and foster business growth. Paper type: Research paper.